PENERAPAN METODE ANP (ANALYTIC NETWORK PROCESS) DALAM RANGKA SELEKSI PEMASOK DAUN TEMBAKAU NA – OOGST DI KOPERASI AGROBISNIS TARUTAMA NUSANTARA – JEMBER - Fatimatuz Zahra; Bambang Herry Purnomo; Nita Kuswardhani (Agroindustrial Technology, University of Trunojoyo Madura, 2015)
Supplier is one the most important and inflluence thing in suplly chain of a companyexistency. Supplier selection has a big role in decision making for getting supplier inimprovement of company’s competitive. Tarutama Nusantara Agrobusiness Cooperative (KopaTTN) is one of the Indonesian company exporting tobacco leaves of Na-Oogst Besuki toEuropean countries. Kopa TTN has Madani Agro Sejahtera (MAS) as a branch company thatfocuse on tobacco Na-Oogst trading. For this reason, MAS should be always increasing itscompetitive by supplier selection. The aim of this research were to get criteria and sub-criteriathat mostly concerned in supplier selection of tobacco leaves and also to get the prior oftobacco leaves supplier by using Analytic Network Process (ANP) methode.. Result showed thatthe prior sub-criteria was physical appearance of material quality criteria.Abdul Wahabmemiliki prioritas tertinggi di antara pemasok lainnya dengan nilai 0,059782; kemudianberturut-turut prioritas tertinggi hingga terendah adalah H. Busyono dengan nilai 0,045026,Henu dengan nilai 0,044384, Miseri dengan nilai 0,034880, Topik dengan nilai 0,010456 danterakhir adalah H. Aminullah dengan nilai 0,003231.